Aspects of the novel - Forster, Edward Morgan (Penguin Book, 1963)
The seven aspects offered for discussion are the story, people, plot, fantasy, prophecy, pattern, and rhythm. The author compares the form and texture of the novel to those of a symphony. As for subject, he expects the work "to reveal the hidden life at its source." Human nature, he concludes, is the novelist's necessary preoccupation